Hb Moscva [β24(B6)Gly→Asp (GGT>GAT), HBB: c.74G>A]: An Unstable Hemoglobin Newly Detected as a De Novo Mutation in a Mauritanian Patient. (2nd January 2018) - Ghaber, Sidi M.; Trabelsi, Nawel; Salem, Mohamed L.; Haddad, Faten; Abba, Aminetou; Darragi, Imen; Abbes, Salem
Abstract: Unstable hemoglobins (Hbs) are a group of Hb disorders that could be the origin of chronic hemolytic anemia. Most of these disorders are caused by point mutations taking place in the globin genes and affecting the stability of the Hb molecule. They are inherited as autosomal dominant diseases and described worldwide. Herein we report a new observation of an unstable variant in the Mauritanian population. The patient was a young girl of Mauritanian origin. She presented with chronic hemolytic anemia with an unknown etiology after being referred to several medical centers. Laboratory investigations based on routine analyses, capillary electrophoresis (CE), cation exchange high performance liquid chromatography (HPLC) and DNA sequencing revealed an abnormal unstable Hb known as Hb Moscva [β24(B6)Gly→Asp (G G T>G A T), HBB : c.74G>A] that occurred as a de novo mutation newly detected in an African girl of Mauritanian origin.